The importance of monitoring and entrepreneurship concept as future direction of microfinance in Malaysia: Case study in the state of Selangor - ﻿Hamdan, ﻿Hamdino; ﻿Othman, ﻿Pazim@Fadzim; ﻿Wan Hussin, ﻿Wan Sabri (Global Research Agency, 2012)
The Economic Crisis of 1997-1998 that invaded the Asian region prompted the Malaysian Government to realize that the dependence on the labor-intensive and capital–intensive modes of production was insufficient to sustain the future economic growth. The future competitiveness of the Malaysian economy depends heavily on the knowledge-based characteristics where entrepreneurial aspects are considered more important for future economic growth and the alleviation of poverty. In support for the entrepreneurial activities among the poor, microfinance1 program is deemed important for the poor to start their business activities in the form of microenterprises. The integration of entrepreneurial concept and microenterprise into microfinance program also contributes towards increasing the effectiveness of the program. Basically, the microfinance program in Malaysia has been administered by various institutions and non-banking government agencies. The most important institutions for this study are Lembaga Zakat Selangor (LZS), Yayasan Basmi Kemiskinan (YBK) Selangor, Amanah Ikhtiar Malaysia(AIM) and Yayasan Tekun Nasional (TEKUN). However, it is doubtful whether this program has achieved its objective in enhancing the socio-economic level of the poor and contributing to the development of entrepreneurial activities. In addition, there have been very few studies to evaluate the importance of monitoring in enhancing the effectiveness of the microfinance program. Therefore, the focus of this study is to evaluate the effectiveness of YBK Selangor, AIM, TEKUN and LZS microfinance programs in increasing the participants’ business income by conducting microenterprise businesses through the adoption of entrepreneurial concept. Based on the univariate and multivariate analyses, the results show that AIM is the most effective microfinance program as it enables the poor to increase their business income and contributes to the development of entrepreneurial activities. Results of the study also show that monitoring, fund size, purpose of loan usage and total income before participating in the microfinance program, are the main factors which influence the level of income that poor people can generate. In addition, Islamic microfinance program which is based on Syariah and Islamic Finance﻿concept has a very high potential in helping the poor to expand and diversify their economic activities, and increase their contribution towards development of entrepreneurial activities.